SAAD MOHAMED, Saad, coord. (2016). Estudios en torno a la traducción del Quijote. Libro conmemorativo del IV centenario de la muerte de Cervantes. Granada: Editorial Comares, 142 p. - Ali Mohamed Abdel-Latif (Dirāsāt Hispānicas, 2020)
Reseña bibliográfica